Highly jet-black carbon black composition
The master bead composition with carbon nanomaterials and additives addresses the dispersibility challenge of highly jet-black carbon blacks, enhancing dispersibility and jet blackness in resin systems for improved processing and color performance.
Patent Information
- Application Number
- JP2021563219
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-23
- Filing Date
- 2020-04-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-04-23
AI Technical Summary
Highly jet-black carbon blacks are difficult to disperse in resin systems due to their inherent particle size and high surface area, leading to high energy consumption and processing challenges, especially in applications requiring high jet blackness.
A master bead composition comprising 50% to 80% carbon nanomaterials and 20% to 50% additives such as mold release agents, UV stabilizers, heat stabilizers, and flame retardants, which are pre-contacted with carbon black to form easily dispersible microparticles, reducing the need for high energy mixing and improving dispersibility.
The master bead composition achieves improved dispersibility and jet blackness in resin systems, reducing dust generation and energy consumption while maintaining excellent color properties, making it suitable for applications like textiles and automotive parts.
Smart Images

Figure 0007617021000002 
Figure 0007617021000003 
Figure 0007617021000004
Abstract
Description
[Technical field]
[0001] background Technical Field The present disclosure relates to carbon black and compositions comprising carbon black that may be useful in applications requiring high jetness. The present disclosure provides compositions useful in high jetness applications, as well as methods for their preparation and use. [Background technology]
[0002] Technical background Carbon black can be used in a variety of applications to impart color. The ability of a carbon black material or a composition containing such a carbon black material to absorb light is called jetness. Often jetness will refer to the color of a material containing carbon black as the only pigment, while tint will refer to a color developed by using a blend of pigments. Carbon blacks with higher jetness can result in a darker composition than low jetness carbon black materials. Spectrographs can be used to evaluate the jetness of a sample. High jetness carbon blacks can also be difficult to disperse in some systems. Thus, there is a need for improved high jetness carbon blacks and compositions containing such high jetness carbon blacks. These and other needs are met by the compositions and methods of the present disclosure. Summary of the Invention
[0003] overview In accordance with the purposes of the present invention, as embodied and broadly described herein, the present disclosure relates in one aspect to a high jetness carbon black material, compositions comprising such a high jetness carbon black material, and processes for the preparation and uses thereof. In one embodiment, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of a carbon nanomaterial and about 20% to about 50% by weight of an additive comprising one or more of the following: a mold release composition, a UV stabilizer, a heat stabilizer and / or an antioxidant, and a flame retardant.
[0004] In another aspect, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of carbon black and about 20% to about 50% by weight of additives comprising one or more of the following: a mold release composition, a UV stabilizer, a heat stabilizer and / or an antioxidant, and a flame retardant. In another aspect, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of piano black and about 20% to about 50% by weight of additives comprising one or more of the following: a mold release composition, a UV stabilizer, a heat stabilizer and / or an antioxidant, and a flame retardant. In another aspect, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of a carbon nanomaterial and about 20% to about 50% by weight of an additive comprising a release composition. In another aspect, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of a carbon nanomaterial and about 20% to about 50% by weight of an additive comprising an amide. In another aspect, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of a carbon nanomaterial and about 20% to about 50% by weight of an additive comprising N,N'-ethylenebis(stearamide).
[0005] In one aspect, the present disclosure provides a master bead composition comprising about 50% to about 80% by weight of a carbon nanomaterial and about 20% to about 50% by weight of additives comprising one or more of the following: a mold release composition, a UV stabilizer, a thermal stabilizer and / or an antioxidant, and a flame retardant, the master bead composition having a jetness (L value) of less than about 3.5 when reduced to about 0.5% to about 1.0% by weight of carbon black loading in the resin. In another aspect, the present disclosure provides a method for preparing a master bead composition, the method comprising contacting about 50% to about 80% by weight of a carbon nanomaterial with about 20% to about 50% by weight of an additive comprising one or more of the following: a mold release composition, a UV stabilizer, a heat stabilizer and / or an antioxidant, and a flame retardant to form a master bead having a plurality of particulates.
[0006] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects and, together with the description, serve to explain the principles of the invention. [Brief description of the drawings]
[0007] [Figure 1A] 1 is a scanning electron microscope (SEM) image of a cross section of a masterbatch extrudate prepared using 30 wt. % Raven 2500 Ultra carbon black in polyamide 6 resin in accordance with various embodiments of the present disclosure. [Figure 1B] 1 is a SEM image of a cross section of a masterbatch extrudate prepared using 20 wt. % Raven 5100 Ultra carbon black in polyamide 6 resin in accordance with various embodiments of the present disclosure. [Figure 1C] 1 is a SEM image of a cross section of a masterbatch extrudate prepared using 20 wt. % Raven 5100 Ultra carbon black and 10 wt. % N,N′-ethylene bis(stearamide) (EBS) in polyamide 6 resin in accordance with various embodiments of the present disclosure. [Figure 2A] FIG. 1 is a transmission electron microscope (TEM) image of a portion of an injection molded color chip prepared from a master bead composition of Raven 2500 Ultra carbon black and EBS, reduced to 0.5 wt. % carbon black loading using polyamide 6, according to various embodiments of the present disclosure. [Figure 2B]FIG. 1 is a TEM image of a portion of an injection molded color chip prepared from a master bead composition of Raven 3000 Ultra carbon black and EBS reduced to 0.5 wt. % carbon black loading using polyamide 6 according to various embodiments of the present disclosure. [Figure 2C] FIG. 1 is a TEM image of a portion of an injection molded color chip prepared from a master bead composition of Raven 5100 Ultra carbon black and EBS reduced to 0.5 wt. % carbon black loading using polyamide 6 according to various embodiments of the present disclosure. [Diagram 3] 1 is a graph illustrating reduced color performance of carbon black masterbatch compositions in accordance with various aspects of the present disclosure. [Figure 4] 1 is a graph illustrating the color performance of carbon black-containing master bead compositions with additives according to various aspects of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Additional aspects of the invention will be set forth in part in the description which follows and in part will be obvious from the description or may be learned by the practice of the invention. The advantages of the invention will be realized and attained by means of the elements and combinations particularly pointed out in the appended claims. It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory and are not restrictive of the invention, as claimed.
[0009] Detailed Description The present invention may be understood more readily by reference to the following detailed description of the invention and the examples included therein. Before the present compounds, compositions, articles, systems, devices, and / or methods are disclosed and described, it is to be understood that they are not limited to specific synthetic methods unless otherwise specified, and are not limited to specific reagents unless otherwise specified, but can of course vary as such. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, example methods and materials are described below. All publications mentioned herein are incorporated by reference to disclose and describe the methods and / or materials in connection with which the publications are cited. Unless otherwise limited, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, example methods and materials are described herein.
[0010] As used herein, unless otherwise noted, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a filler" or "a solvent" includes a mixture of two or more fillers or solvents, respectively. Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values are expressed as approximations, it will be understood that the particular value forms another embodiment by using the antecedent "about." It will be further understood that the endpoints of each range are significant both in relation to the other endpoint and independently of the other endpoint. It is also understood that there are a number of values disclosed herein, and that each value is disclosed as "about" that particular value in addition to the value itself. For example, if a value of "10" is disclosed, then "about 10" is also disclosed. It is also understood that each unit between two particular units is also disclosed. For example, if 10 and 15 are disclosed, then 11, 12, 13, and 14 are also disclosed. As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and the description includes instances where said event or circumstance occurs and instances where it does not occur.
[0011] Disclosed are the components used to prepare the compositions of the invention as well as the compositions themselves used within the methods disclosed herein. These and other materials are disclosed herein, and when combinations, subsets, interactions, groups, etc. of these materials are disclosed, it is understood that although specific references to various individual and collective combinations and permutations of these compounds may not be expressly disclosed, each is expressly contemplated and described herein. For example, when a particular compound is disclosed and discussed, and many modifications that can be made to a number of molecules that include the compound are discussed, what is expressly contemplated is each and every combination and permutation of the compound and possible modifications unless otherwise noted. Thus, when a class of molecules A, B, and C is also disclosed, and a class of molecules D, E, and F, and an example of a combination molecule, AD, are also disclosed, each is individually and collectively contemplated and means a combination, even if each is not individually listed, and AE, AF, BD, BE, BF, CD, CE, and CF are considered to be disclosed. Similarly, any subset or combination of these is disclosed. Thus, for example, the subgroups AE, BF, and CE are considered to be disclosed. This concept applies to all aspects of this application including, but not limited to, steps in methods of making and using the compositions of the invention. Thus, where there are various additional steps that may be implemented, it is to be understood that each of these additional steps may be implemented in any specific embodiment or combination of embodiments of the methods of the invention.
[0012] Each of the materials disclosed herein is commercially available and / or methods for its preparation are known to those of skill in the art. It is understood that the compositions disclosed herein have certain functions. Disclosed herein are certain structural requirements for performing the disclosed functions, and it is understood that there are a variety of structures that can perform the same functions associated with the disclosed structures, and that these structures typically achieve the same results. Unless indicated otherwise, parts are parts by weight, temperature is in ° C. or is at ambient temperature, and pressure is at or near atmospheric.
[0013] As briefly described above, the present disclosure provides high jetness carbon blacks and compositions containing such high jetness carbon blacks, along with methods for preparing and uses thereof. There is an increasing market demand for high jetness engineering plastic compositions, especially for fiber and automotive applications, which can be met with high surface area carbon blacks. These carbon blacks may also be referred to as piano blacks in the art. Although these carbon blacks can impart excellent jetness properties to the resulting compositions, their inherent particle size (i.e., fineness) and high surface area can make them very difficult to disperse. In one aspect, the high van der Waals interactions between carbon black aggregates and the limited affinity between carbon black and conventional polymer resins can require high energy input to achieve good dispersibility within the polymer system. Good dispersibility is important for these applications, but can be difficult when using conventional compounding methods.
[0014] Applications using carbon black-filled engineering resins typically require a package of additives to overcome the challenges of dispersing and processing carbon black in the resin composition and to optimize their performance for specific applications. The specific additive or combination of additives may vary depending on the resin or resins used and the specific application, but these additive compositions can be characterized based on the function or property they impart to the final resin / carbon black composition. In various conventional systems, one or more of the following additives can be used: (1) mold release compositions that can be used in extrusion or molding processes to prevent adhesion to metal surfaces of the finished part, (2) UV stabilizers used to extend the outdoor life of plastic parts, (3) heat stabilizers and / or antioxidants used to protect the resin from thermal and oxidative degradation during processing, and (4) flame retardants used to prevent or slow the spread of fires. In other embodiments, other additives can be used in addition to or in place of any of the above. In still other embodiments, multiple additives of a single type or multiple additives of different types can be used in the composition.
[0015] Carbon black materials can be inherently difficult to handle due to their fineness and dusting properties. They can also be difficult to disperse in plastics. High energy mixing is typically required to achieve good carbon black dispersion in most resin systems. Many users of carbon black materials lack the expensive equipment and / or expertise to efficiently disperse carbon black in these resin systems. As a result, some users choose to use masterbatch compositions, where the carbon black is dispersed in the resin system at a higher concentration than is necessary for use in making the final product. These concentrates can be prepared by companies that have the equipment and knowledge to efficiently disperse carbon black materials. Once the carbon black is well dispersed, even at high concentrations, additional resin can be added to dilute the carbon black concentration. End users can purchase a carbon black masterbatch composition and then dilute or reduce the composition by adding additional resin. The energy required to incorporate that additional resin and disperse the predispersed carbon black in the remaining resin is significantly less than the energy required to form the masterbatch. Masterbatch materials also have the added advantage of being easier to handle and less dusting since the carbon black is incorporated into the resin matrix. The present disclosure is an alternative to traditional masterbatch technology, but provides a resin-free pre-dispersed carbon black that is similarly easier to handle and can be easily dispersed into a resin system by the end user.
[0016] In one embodiment, the present disclosure provides a combination of carbon black, one or more additives, and any resin or plastic material. In such an embodiment, the one or more additives are intended to improve the dispersibility of the carbon black in the resin. In another embodiment, the composition does not include a resin, but includes only one or more carbon blacks and one or more additives. In some embodiments, one or more of these additives may be conventional additives used for one or more of the above purposes. In such an embodiment, the present invention contemplates the use of such additive or additives at higher concentrations than normal methods and applications, and as a carrier for the carbon black, and not simply as a mold release agent, UV stabilizer, heat stabilizer, and / or flame retardant. Thus, in some embodiments, the concentration of any one additive or combination of additives is contemplated to be higher than that used in the art for their normal purposes.
[0017] In one embodiment, an additive or mixture of additives can be used with the carbon black and resin to improve dispersion during compounding. In another embodiment, the carbon black can be pre-contacted with an additive or mixture of additives before contacting with the resin. Such pre-contacted carbon black can be referred to as master beads in various embodiments. In such embodiments, the treated carbon black can be packaged and / or sold and then mixed with the resin. In yet another embodiment, a master batch (i.e., concentrate) can be prepared containing the carbon black, resin and additive or additives, where the carbon black is well dispersed in the master batch composition. In such embodiments, the end user can reduce the master batch by contacting the master batch composition with additional resin to dilute the concentrated carbon black and / or additive(s) in the master batch composition.
[0018] Without wishing to be bound by theory, it is believed that the use of carbon black and additives as described herein can improve the compatibility of the carbon black in the resin system. In another aspect, it is believed that the carbon black and additive compositions described herein can include a co-continuous morphology. The carbon black of the present invention can include any carbon black suitable for use in applications requiring high jetness. In one embodiment, the carbon black is a furnace carbon black. In one embodiment, a single high jetness carbon black can be used. In another embodiment, two or more carbon blacks can be used, with at least one of the carbon blacks being a high jetness carbon black. In yet another embodiment, two or more high jetness carbon blacks can be used. In yet another embodiment, the high jetness carbon black can replace all or a portion of other conventional carbon blacks and / or other pigments or dyes in the composition.
[0019] In one embodiment, the present invention includes a piano black. In various embodiments, the piano black is, for example, at least about 175 mm. 2 / g, at least about 200m 2 / g, at least about 225m 2 / g, at least about 250m 2 / g, at least about 300m 2 / g, at least about 350m 2 / g, at least about 400m 2 / g, at least about 450m 2 / g, at least about 500m 2 In another embodiment, the piano black comprises a high surface area carbon black having a nitrogen surface area (NSA) of about 175 to about 700 m / g or more. 2 / g, about 200~600m 2 / g, about 250~550m 2 / g, about 300~600m 2 / g, about 350~600m 2 / g, about 400~650m2 / g, about 450~575m 2 / g, or about 500 to about 650 m 2 In another embodiment, the piano black comprises a carbon black having an NSA of about 150 to about 400 m / g. 2 / g, or about 200 to about 350 m 2 The piano black may include carbon black having a statistical thickness surface area (STSA) of about 100 ml / 100 g, about 60 to about 120 ml / 100 g, or about 65 to about 105 ml / 100 g, or about 80 to about 105 ml / 100 g. In other embodiments, the piano black may have an NSA, STSA, and / or OAN outside the ranges listed herein. In other embodiments, the piano black may have an unmodified surface. In still other embodiments, the piano black may have a modified surface, for example, oxidized via ozone, acid, or hydrogen peroxide, or functionalized with other groups (e.g., amines, carboxylic acids, etc.). There are numerous examples of carbon black surface modifications in the literature, each of which is contemplated in the present invention. Carbon blacks such as those for use in the present invention are commercially available, for example, from Birla Carbon USA, Inc., Marietta, Georgia, USA.
[0020] NSA means Nitrogen Surface Area, which may be measured in accordance with ASTM D6556, and is a measure of the total surface area of a carbon black sample accessible to nitrogen, including porosity based on BET theory. STSA means the statistical thickness surface area or external surface area of a carbon black sample accessible to plastic or other media, and may be measured in accordance with ASTM D6556. OAN means Oil Absorption, and is intended to provide an indication of the structure, or aggregate size, of a carbon black grade. OAN may be measured in accordance with ASTM D2414. In other embodiments, the carbon black of the present invention can be replaced in whole or in part with one or more other carbon nanomaterials, such as, for example, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon fibers, and graphene. Thus, in one embodiment, the composition can include a carbon nanomaterial and one or more additives.
[0021] In one embodiment, the present invention also includes conventional mold release additives or analogs or derivatives thereof. In various embodiments, such mold release agents can include amides, such as primary, secondary, and / or tertiary amides, or amines. In one embodiment, the additive can include ethylene bisstearamide (EBS) (see below as compound (I)). In another embodiment, the additive can include a wax, such as polyethylene wax. In yet another embodiment, the additive can include one or more other conventional mold release agents. In other embodiments, any one or more of the individual additives listed or contemplated herein can be combined to form an additive. In one embodiment, multiple mold release agents or other additives can be used together. Mold release agents are typically chemically compatible with the resin matrix and often have a lower molecular weight than the resin compound. [ka]
[0022] In another embodiment, the present invention includes a UV stabilizer additive or an analog or derivative thereof. In various embodiments, such UV stabilizer additives can include benzotriazoles, hindered amine light stabilizers (HALS), and / or other conventional UV stabilizer additives. In one embodiment, multiple UV stabilizer additives or other additives can be used together. In another aspect, the present invention includes a flame retardant additive or an analog or derivative thereof. In various aspects, the flame retardant additive can be used alone or in combination with other flame retardant additives or other additives. In another embodiment, the present invention includes a mixture of any two or more types of additives listed herein or commonly used in the processing of materials, including piano black. In various embodiments, the composition can include any mixture of additive materials. In another embodiment, any one or more of the additives or additive types listed herein can be specifically excluded from the composition. These additives may be used in the processing of conventional carbon black-containing resin materials, but are typically used at low levels, such as, for example, less than about 1,000 ppm or less than about 500 ppm. Because these additive materials typically have a lower molecular weight than the resin with which they are mixed and are typically soluble and / or compatible in the resin, the present invention contemplates their use as carriers for preparing master beads or master batch materials, or as surface modifiers for carbon black to facilitate and improve wetting and dispersibility.
[0023] Master Bead Composition In various embodiments, the weight ratio of carbon black to any individual additive or combination of additives when multiple additives are present can be from about 95:5 (carbon black:additive) to about 50:50, e.g., about 95:5, 90:10, 85:15, 80:20, 75:25, 70:30, 65:35, 60:40, 55:45, or 50:50. In other embodiments, the weight ratio of carbon black to any individual additive or combination can be from about 90:10 to about 50:50, from about 85:15 to about 40:60, from about 75:25 to about 50:50, from about 70:30 to about 45:55, from about 60:40 to about 40:60, from about 80:20 to about 30:70, or from about 75:25 to about 60:40. In other embodiments, the weight ratio of carbon black to any individual additive or combination of additives can be higher or lower than any of the values or ranges recited herein. In another embodiment, the ratio of carbon black to additives can be about 5:1, 4.5:1, 4:1, 3.5:1, 3:1, 2.5:1, 2:1, 1.5:1, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, 1:3.2, 1:3.4, 1:3.6:1:3.8, 1:4, 1:4.2, 1:4.4, 1:4.6, 1:4.8, or 1:5. In other embodiments, the ratio of carbon black to additive or combination of additives may be higher or lower than any particular value or range recited herein. In one embodiment, the above weight ratios may refer to a master bead composition that includes carbon black and one or more additives. In another embodiment, the above weight ratios of carbon black to additives may refer to a master batch composition that also includes one or more resin materials.
[0024] In one embodiment, an additive or mixture of additives can be present in the final composition at a concentration of at least about 5,000 ppm, at least about 6,000 ppm, at least about 7,000 ppm, at least about 8,000 ppm, at least about 9,000 ppm, at least about 10,000 ppm, or more. In another embodiment, an additive or mixture of additives can be present in a range from any of the above lower limits up to about 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, 50,000 ppm, 75,000 ppm, 100,000 ppm, 150,000 ppm, 200,000 ppm, 250,000 ppm, 300,000 ppm, 350,000 ppm, 400,000 ppm, 450,000 ppm, 500,000 ppm, or more.
[0025] In one embodiment, when using one or more of the additives and piano black as described herein, the carbon black loading can be increased by at least about 40%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, or more by weight. In another embodiment, the carbon black loading can be increased to a level of about 40% to about 75% by weight, about 40% to about 80% by weight, about 40% to about 85% by weight, about 50% to about 85% by weight, about 50% to about 75% by weight, about 55% to about 75% by weight, about 55% to about 80% by weight, about 60% to about 80% by weight, about 60% to about 85% by weight, about 60% to about 75% by weight, about 65% to about 85% by weight, about 65% to about 80% by weight, or about 65% to about 75% by weight. In other embodiments, the amount of carbon black in the master bead composition can be about 60% to about 80% by weight and the amount of additive can be about 20% to about 40% by weight. In other embodiments, the carbon black and / or additive loading can be higher or lower than any of the specific values or ranges listed herein. In another aspect, the use of high loadings of carbon black, as provided herein, can be used while still maintaining excellent dispersibility.
[0026] Masterbatch Composition As mentioned above, a masterbatch composition can be prepared that includes carbon black, one or more additives as described herein, and one or more resin materials. In one embodiment, the masterbatch can be prepared by contacting one or more resin materials with master beads as described above. In another embodiment, the masterbatch composition can be prepared by contacting carbon black, one or more additives as described herein, and one or more resin materials. In various embodiments, the resin materials of the masterbatch composition or used to reduce as the masterbatch composition can include any conventional resin materials including, for example, polycarbonates, polyamides, polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate, copolymers such as styrene-acrylonitrile, and terpolymers such as acrylonitrile butadiene styrene. In other embodiments, other resin materials not specifically listed herein can be used in addition to or in place of any of the resin materials listed herein. In one embodiment, the carbon black and / or one of the additives can be selected based on their compatibility and / or miscibility with a particular resin system. For example, Ravn 3500 Ultra is an ozonated carbon black that has oxygen-containing functional groups on its surface. Ozonation can improve the chemical compatibility of the carbon black with certain resins, such as polyamides, thus allowing for improved dispersibility of the carbon black in the resin.
[0027] In various embodiments, the ratio of carbon black to any one or more additives in the master batch composition can be the same as the master bead composition comprising carbon black and one or more additives as described above. In other embodiments, the concentration of carbon black and the one or more additives can be proportionally decreased as resin material is added to the composition. For example, a master bead composition comprising 70% carbon black and 30% additives by weight can be contacted with a portion of the resin material to provide a composition comprising 50% resin, 35% carbon black, and 15% additives by weight. In various embodiments, the carbon black in the master batch composition can comprise from about 20% to about 50%, from about 20% to about 40%, from about 25% to about 60%, from about 30% to about 40%, or from about 20% to about 35%, by weight of the composition. In other embodiments, the carbon black can be present in concentrations greater or less than the values or ranges described herein. In another embodiment, the additive or mixture of additives in the masterbatch composition can be present in a concentration of about 5% to about 35%, about 5% to about 10%, about 5% to about 20%, about 10% to about 35%, about 10% to about 25%, about 10% to about 20%, about 15% to about 25%, about 15% to about 30%, about 20% to about 35%, or about 25% to about 35% by weight. In another embodiment, the additive or mixture of additives in the masterbatch composition can be present in a concentration higher or lower than any particular value or range recited herein. In still other embodiments, the resin or mixture of resins in the masterbatch composition can comprise about 40% to about 90%, about 50% to about 80%, about 50% to about 70%, about 45% to about 75%, about 55% to about 85%, about 50% to about 60%, about 60% to about 75%, or about 65% to about 80% by weight of the masterbatch composition. In still other embodiments, the resin or mixture of resins in the masterbatch composition can be present in a concentration greater or less than any particular value or range recited herein.
[0028] In various embodiments, the masterbatch composition and / or the final composition, in which the masterbatch or masterbeads are contacted with the resin to achieve the final target resin concentration, can be prepared using one or more conventional mixing techniques, including, for example, a twin-screw extruder, and / or a high torque compounder, such as, for example, a Farrell continuous mixer or a Banbury mixer. It is understood that different mixing and / or compounding equipment can handle different volumes and concentrations of materials, and one of ordinary skill in the art in possession of this disclosure can easily select the appropriate mixing and / or compounding technique and / or equipment for a particular material. For example, it may be possible to obtain a higher carbon black loading using a Banbury-type mixer than with a twin-screw extruder or continuous mixer.
[0029] final composition As mentioned above, the final composition can be prepared to achieve a target final resin concentration, where one or more resins are added to the mixture of carbon black and one or more additives, as described herein. In such embodiments, the additive or mixture of additives can be present in the final composition (e.g., reduced composition) at a concentration of about 2,000 ppm to about 10,000 ppm, about 6,000 ppm to about 10,000 ppm, about 7,000 ppm to about 15,000 ppm, about 5,000 ppm to about 9,000 ppm, about 8,000 ppm to about 12,000, or about 10,000 ppm to about 50,000 ppm. In another embodiment, such final compositions can have a carbon black concentration of about 0.5%, 0.6%, about 0.7%, about 0.8%, about 0.9%, about 1%, about 1.1%, about 1.2%, about 1.3%, about 1.4%, about 1.5%, about 1.6%, about 1.7%, about 1.8%, about 1.9%, about 2%, about 2.1%, about 2.2%, about 2.3%, about 2.4%, about 2.5%, or more by weight. In other embodiments, the concentration of carbon black and / or one or mixture of additives can be higher or lower than any specific value or range recited herein.
[0030] In one embodiment, the masterbatch sample prepared according to the present invention can contain about 1% by weight of carbon black and less than about 5,000 ppm of additives, such as EBS, in the final application. In another embodiment, such compositions can exhibit good mold release properties, excellent carbon black dispersion, and can impart high jetness to the resulting application. In yet another embodiment, an additive or combination of additives described herein can be used in place of or in addition to being incorporated into the mixture prior to compounding in the bead process. In such an embodiment, an additive or additive package can be premixed with the carbon black to provide a readily dispersible carbon black for the intended resin or application. In one embodiment, the use of one or a combination of additives described herein can improve the dispersibility of carbon black in a resin material while maintaining good masstone and / or undertone properties. In other embodiments, the master beads of the present invention can exhibit improved handleability while also improving dispersibility in the resulting material. In such embodiments, the master beads exhibit reduced dusting and / or fines when handled or transported, resulting in improved environmental conditions and reduced product loss as compared to conventional carbon black materials.
[0031] Color Characteristics Carbon blacks can impart various color characteristics to materials with which they are mixed. For example, carbon black is often added to plastics to impart a black color ("jet black"). Carbon blacks with higher jetness appear blacker than carbon blacks with lower jetness characteristics. Although carbon black is traditionally thought of as black, when incorporated into various materials it can impart a range of colors, called undertones, from blue-black to brown-black. These color properties can be influenced by the primary particle size, surface area, and aggregate size of a particular carbon black. Finally, the dispersibility of the carbon black in a resin or other matrix can greatly affect the color properties imparted to the resulting composition. Color properties can be quantitatively measured using a variety of instrumental methods. Hunter color analyzers, such as the Hunter Lab Compuscan Reflectance Spectrometer in specular reflection excluded mode with a 0 / 45° geometry, use a three-dimensional space to define color properties. Along the first axis, the L value ranges from 0 (jet black) to 100 (white) and indicates color density; along the second axis, the "a" value ranges from -a (green) to +a (red); and along the third axis, the "b" value ranges from -b (blue) to +b (yellow). In carbon black, the undertone is typically referred to as blue or brown, compared to a control sample.
[0032] In various embodiments, the use of the master bead or master batch compositions described herein can provide improved dispersion of carbon black within a resin system and / or improved color performance, such as improved jetness. In various embodiments, a carbon black filled resin system, including one or more additives, when reduced to a carbon black concentration of 0.5% to 1.0% by weight, as described herein, can exhibit an L value (jetness) of less than about 5, less than about 4.5, less than about 4, less than about 4, less than about 3.8, less than about 3.6, less than about 3.4, less than about 3.4, less than about 3.2, less than about 3.0, less than about 2.9, less than about 2.8, less than about 2.7, less than about 2.6, or less than about 2.5. In other embodiments, such compositions can exhibit an L value of about 2.5 to about 5, about 2.5 to about 4.5, about 2.5 to about 4, about 2.5 to about 3.8, about 2.5 to about 3.6, about 2.5 to about 3.4, about 2.5 to about 3.2, about 2.5 to about 3, 2.5 to about 2.9, 2.5 to about 2.8, about 2.5 to about 2.7, or about 2.5 to about 2.6. In one embodiment, such systems can include a polyamide resin, such as polyamide 6. In other embodiments, such systems can include one or more other resin materials. Thus, in various embodiments, the master bead technology of the present disclosure can provide one or more of improved dispersibility in resin systems, improved jetness, reduced dusting, and improved handling properties relative to carbon black. EXAMPLES
[0033] Various exemplary embodiments of the present invention are described in detail below. These embodiments are illustrative and are not intended to limit the scope of the present invention. For each of the following examples, the following methods, equipment, and conditions were used unless otherwise indicated. Compounding was performed in polyamide 6 resin (AdvanSix, Aegis, H82O2NLB, 96% SAV=2.61) on a PRISM twin screw extruder (16mm, 25:1) set at 260°C and immediately pelletized. Prior to compounding, carbon black and PA6 resin were dried in an oven at 160°C overnight and in a vacuum oven at 80°C for up to 3 days, respectively, to minimize moisture content.
[0034] Example 1 - Masterbatch composition and SEM analysis A first masterbatch ("A") was prepared using a twin screw extruder and polyamide 6 resin as described above, using 30% by weight of Raven 2500 Ultra carbon black. This masterbatch extrudate was cut with a razor blade and examined in cross section using a scanning electron microscope (SEM) to evaluate carbon black dispersion. The extrudate examined contained several areas of poorly dispersed carbon black, which may be common in resin systems containing high surface area carbon black, as shown in Figure 1A. A second masterbatch ("B") was prepared as described above, except that 20 wt. % Raven 5100 Ultra carbon black was used in polyamide 6 resin. The masterbatch extrudate from the twin screw extruder was examined and also had some regions of poorly dispersed carbon black, as shown in Figure 1B. A third masterbatch ("C") was prepared as described above, except using 20 wt. % Raven 5100 Ultra carbon black and 10 wt. % N,N'-ethylenebis(stearamide) (EBS, available from Sigma Aldrich) in polyamide 6 resin. The masterbatch extrudate from the twin screw extruder was examined and found to have significantly improved carbon black dispersion over Masterbatch B, which did not contain EBS.
[0035] Example 2 - Masterbatch analysis by TEM The carbon black master bead compositions used Raven 2500 Ultra carbon black, Raven 3000 Ultra carbon black, and Raven 5100 Ultra carbon black, each containing about 55% to about 65% carbon black by weight, with the remainder being N,N'-ethylenebis(stearamide). Each master bead composition was subsequently reduced to a carbon black loading of 0.5% by weight using polyamide 6 resin and then injection molded into color chips at 260°C. Slices of the resulting chips were prepared and analyzed by transmission electron microscopy (TEM) to evaluate carbon black dispersion. As shown in Figures 2A, 2B, and 2C, respectively, each of the reduced compositions exhibited excellent dispersion of carbon black, demonstrating the benefits of the additive and master bead technology in improving carbon black dispersion.
[0036] Example 3 - Color Performance Three masterbatch compositions were prepared in polyamide 6 using three piano blacks (Raven 3500 Ultra, Raven 5100 Ultra, and Raven 5100 with ESB), each as in Example 1. The carbon black loading in each masterbatch composition was 20 wt%, and the ESB concentration in the third masterbatch composition was 10 wt%. Each of the three masterbatch compositions was then reduced to a carbon black loading of 1.0 wt% and analyzed using a Hunter color analyzer as described herein. The L values for the three compositions were 5.6 (Raven 3500 Ultra), 3.3 (Raven 5100 Ultra), and 3.1 (Raven 5100 Ultra with EBS). As shown in Figure 3, the piano blacks all showed excellent jetness and blue undertone color performance consistent with their surface areas. Raven 5100 Ultra was significantly jeter than Raven 3500 Ultra because Raven 5100 Ultra has a much higher surface area. Analysis of the masterbatch compositions by SEM shows that the presence of EBS improves the macroscopic dispersibility of the Raven 5100 Ultra carbon black with fewer carbon black agglomerates in the masterbatch. This improved dispersibility and lack of agglomerates can be important in certain automotive applications.
[0037] Example 4 - Color Performance The three color chips prepared in Example 2, each having a carbon black concentration of 0.5% by weight, were prepared from master beads containing carbon black and EBS, and were analyzed using a Hunter color analyzer as described herein. The L values for the three compositions were 4.7 (Raven 2500 Ultra with EBS), 4.5 (Raven 3000 Ultra with EBS), and 2.9 (Raven 5100 Ultra with EBS). As in Example 3, each of these high color carbon blacks provided excellent jetness and undertone color performance. By increasing the surface area from Raven 2500 Ultra to Raven 3000 Ultra to Raven 5100 Ultra, the carbon blacks showed improved jetness. This jetness was achieved by the excellent dispersibility resulting from the addition of EBS, as shown in the TEM micrographs of Figures 2A-C.
[0038] It will be apparent to those skilled in the art that various modifications and variations can be made in the present invention without departing from the scope or spirit of the invention. Other embodiments of the invention will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered as exemplary only, with a true scope and spirit of the invention being indicated by the following claims. Yet another aspect of the present invention may be as follows. [1] A master bead composition comprising about 50% by weight to about 80% by weight of a carbon nanomaterial and about 20% by weight to about 50% by weight of an additive including one or more of a release composition, a UV stabilizer, a heat stabilizer and / or an antioxidant, and a flame retardant. [2] The master bead composition according to [1], wherein the carbon nanomaterial constitutes at least about 60% by weight of the composition. [3] The master bead composition according to [1], wherein the carbon nanomaterial constitutes at least about 70% by weight of the composition. [4] The master bead composition according to [1], wherein the carbon nanomaterial constitutes at least about 75% by weight of the composition. [5] The master bead composition according to [1], wherein the carbon nanomaterial includes carbon black. [6] The master bead composition according to [5], wherein the carbon black comprises furnace carbon black. [7] The master bead composition according to [5] above, wherein the carbon black is oxidized. [8] The master bead composition according to [5], wherein the carbon black includes piano black. [9] The master bead composition according to [1], wherein the carbon nanomaterial comprises carbon nanotubes.
[10] The master bead composition according to [1], wherein the additive comprises an amide.
[11] The master bead composition according to [1], wherein the additive comprises N,N'-ethylenebis(stearamide).
[12] The master bead composition according to [1] above, wherein the additive comprises a wax.
[13] The master bead composition according to [1], wherein the composition does not contain wax.
[14] The master bead composition according to [1] above, wherein the composition does not contain a resin.
[15] The master bead composition according to [1] above, which consists essentially of carbon black and an amide.
[16] The master bead composition according to [1] above, having a jetness (L value) of less than about 3.5 when the carbon black loading in the resin is reduced to about 0.5% to about 1.0% by weight.
[17] The master bead composition according to
[16] , wherein the resin comprises a polyamide resin.
[18] The master bead composition according to
[16] above, having a jetness (L value) of less than about 3.
[19] A method for preparing a master bead composition, comprising contacting about 50% by weight to about 80% by weight of a carbon nanomaterial with about 20% by weight to about 50% by weight of an additive including one or more of a release composition, a UV stabilizer, a heat stabilizer and / or an antioxidant, and a flame retardant to form a master bead having a plurality of microparticles.
[20] The method according to
[16] , wherein the carbon nanomaterial comprises carbon black.
Claims
1. A master bead composition comprising 50% to 80% by weight of carbon black and 20% to 50% by weight of an additive comprising an amide-containing release agent.
2. 2. The master bead composition of claim 1, wherein said carbon black comprises at least 60% by weight of said composition.
3. 2. The master bead composition of claim 1, wherein said carbon black comprises at least 70% by weight of said composition.
4. 2. The master bead composition of claim 1, wherein said carbon black comprises at least 75% by weight of said composition.
5. 10. The master bead composition of claim 1, wherein the carbon black comprises furnace carbon black.
6. 10. The master bead composition of claim 1, wherein the carbon black is oxidized.
7. 10. The master bead composition of claim 1, wherein the carbon black comprises piano black.
8. 2. The master bead composition of claim 1, wherein the amide-containing release agent comprises N,N'-ethylene bis(stearamide).
9. The master bead composition of claim 1 , wherein the additive further comprises a wax.
10. The master bead composition of claim 1 , wherein the composition is wax-free.
11. The master bead composition of claim 1 , wherein the composition is resin-free.
12. 2. The master bead composition of claim 1 consisting essentially of said carbon black and said amide-containing release agent.
13. 10. The master bead composition of claim 1, having a jetness (L value) of less than 3.5 when reduced to a carbon black loading of 0.5% to 1.0% by weight in the resin.
14. The master bead composition of claim 13, wherein the resin comprises a polyamide resin.
15. The master bead composition of claim 13 having a jetness (L value) of less than 3.
16. 1. A method for preparing a master bead composition, comprising contacting 50% to 80% by weight of carbon black with 20% to 50% by weight of an additive comprising a release agent comprising an amide to form a master bead having a plurality of particulates.
Citation Information
Patent Citations
Resin composition for coloring
JP1997235504A
dispersible carbon black pellets
JP1998505368A
Carbon nanotube composition
JP2007231219A
Process for improving carbon black dispersion
US20130018137A1